2019
DOI: 10.1007/s10546-019-00428-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Feasibility of Using Large-Eddy Simulations for Real-Time Turbulent-Flow Forecasting in the Atmospheric Boundary Layer

Abstract: We investigate the feasibility of using large-eddy simulation (LES) for real-time forecasting of instantaneous turbulent velocity fluctuations in the atmospheric boundary layer. Although LES is generally considered computationally too expensive for real-time use, wall-clock time can be significantly reduced by using very coarse meshes. Here, we focus on forecasting errors arising on such coarse grids, and investigate the trade-off between computational speed and accuracy. We omit any aspects related to state e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…While these studies achieved successful dynamic power production increases over baseline operation, the computational expense of adjoint LES is similar to standard LES and is currently a challenge to use in real-time wind farm control. Bauweraerts and Meyers (2019) showed that coarse LES can potentially be used for real-time prediction and control but this requires future investigation and is not the focus of the present study. Ciri et al (2017) used a model-free formulation and dynamic control to increase the power production of a model wind farm and found that downstream wind turbines may also need to change their operational strategy to increase farm performance.…”
Section: Introductionmentioning
confidence: 95%
“…While these studies achieved successful dynamic power production increases over baseline operation, the computational expense of adjoint LES is similar to standard LES and is currently a challenge to use in real-time wind farm control. Bauweraerts and Meyers (2019) showed that coarse LES can potentially be used for real-time prediction and control but this requires future investigation and is not the focus of the present study. Ciri et al (2017) used a model-free formulation and dynamic control to increase the power production of a model wind farm and found that downstream wind turbines may also need to change their operational strategy to increase farm performance.…”
Section: Introductionmentioning
confidence: 95%
“…Diffusive and convective terms are discretized using second-order central differences and a blend of third-order QUICK (10 %) and fourth-order central differences (90 %), respectively. The blended scheme for the convective term was shown to provide sufficient numerical stability while keeping numerical diffusion to a minimum (Troldborg et al, 2010;Bechmann et al, 2011). The pressure correction is solved using the SIMPLE algorithm.…”
Section: Ellipsys3dmentioning
confidence: 99%
“…In the transition region, an internal boundary layer grows from the height of the wind farm at z = z h until it reaches the final boundary layer height at z = δ. The classical internal boundary layer growth model dictates that: (34) until δ ibl = δ. The friction velocities (30) and (31) and planar-averaged velocity (32) evolve with streamwise distance x, where δ is replaced with the internal boundary layer height δ ibl (x).…”
Section: The Steady-state Model For Design Applicationsmentioning
confidence: 99%
“…The simplest models are discrete-time extensions of steady-state wake models [31] and continuous-time one-dimensional models [8,32]. Higher fidelity, yet more computationally-expensive, models include two-dimensional Reynolds-averaged Navier-Stokes (RANS) simulations [33] and very coarse large-eddy simulations (LES) [34].…”
Section: Introductionmentioning
confidence: 99%